SIMILE, HYPERBOLE, PERSONIFICATION AND METAPHOR USED IN GAYLE FORMAN’S IF I STAY - Padillah, Evi Nur; Firmawan, Hendro; Purwaningsih, Endang (Universitas Gunadarma, 2016)
Novel is one type of literary works. Novel as a fiction offers an imaginative world that is not much different with the reality. In process of writing, the authors use figurative language to convey the ideas. The use of appropriate figurative language will give the effect of aesthetic, so the readers will be more interested to know and imagine what the actual meaning from that figurative language which is conveyed. This research focuses on investigating the four kinds of figurative language, they are simile (clear and unclear similarity), hyperbole, personification and metaphor in the novel entitled If I Stay by Gayle Forman. The aims of this research are to find out the characteristics of simile (clear and unclear similarity), hyperbole, personification, and metaphor and to find out the most frequently figure of speech category used in If I Stay’s novel. The study uses a descriptive qualitative method in analyzing the figures of speech in the If I Stay’s novel. As the conclusion, clear similarity has characteristics like there are vehicle, tenor, connector (like, as such, etc), and contain the details of the similarity, while unclear similarity has characteristics which there are vehicle, tenor, connector (like, as such, etc), and do not contain the details of the similarity. Hyperbole has the characteristic that is overstatement or say something much bigger than the real. Personification has the characteristic that is human being or gives human attributes to nonhuman. The characteristics of metaphor which there are vehicle and tenor but there isn’t connector (like, as such, etc). From the four kinds of figures of speech are taken to be analysis, there are 169 times of figurative language occurrence, 74 times (44%) of simile, 72 times (43%) of hyperbole, 12 times ( 7%) of personification and 11 times ( 6%) of metaphor. The most dominant figurative language category used in this novel is simile.Keywords: Figurative Speech, Simile, Hyperbole, Personification, Metaphor.